PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID DENGAN APLIKASI FIIWRITE PADA MATERI PENYAJIAN DATA DI KELAS VII SMP SWASTA SANTO YOSEP MEDAN - Sitanggang, Maria (Jurnal Pendidikan Matematika Undiksha, 2022)
This study aims to develop and find out the feasibility, practicality, and effectiveness of android-based learning media with fiiwrite application on data presentation material in the 7th grades of Saint Joseph’s Junior High School Medan. The model used in this research was the ADDIE model consisting of 5 stages: Analyze (A), Design (D), Development (D), Implementation (I), Evaluation (E). The assessment instrument used is a questionnaire to test the feasibility of an android-based learning media product with a fiiwrite application. The teacher and 8th students from 7D grades will give a response questionnaire to determine the practicality of the media and 21 students from 7C grades will give a pretest and posttest to decide the effectiveness of the media. The results of this development get android-based learning media with the fiiwrite application on data presentation material in 7th grades of Saint Joseph’s Junior High School Medan from media assessment experts obtained a very feasible category with a percentage of 83.5%, an assessment from material experts gets an average of 92.85% with very feasibly category, a teacher and student responses obtained an average of 87.2%, and for the assessment of the effectiveness of learning media get a percentage of 90.47% with very practically category. From the results of the test, be concluded that android-based learning media with fiiwrite application on the material presentation of data development can use as a mathematical learning medium of data presentation material in VII grades of junior high school.